2015
DOI: 10.1007/s13197-015-1888-y
|View full text |Cite
|
Sign up to set email alerts
|

Flavouring compounds in Indian potato snacks

Abstract: Market for processed potato products is rising day by day. Flavour plays important role in decision making by consumers due to their preferences for better tasting food. In potato and potato products, glutamic acid, aspartic acid, guanosine 5′-monophosphate (GMP) and adenosine 5′-monophosphate (AMP) are the major umami compounds which contribute towards flavour. Therefore, umami 5′ nucleotides (AMP+GMP) were estimated from local potato products available as common fried products in the Indian markets and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Remaining experimental conditions and mobile phase were kept the same as optimized by Raigond et al (2015) for calculating the major flavoring compounds (AMP ? GMP).…”
Section: Flavor Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Remaining experimental conditions and mobile phase were kept the same as optimized by Raigond et al (2015) for calculating the major flavoring compounds (AMP ? GMP).…”
Section: Flavor Analysismentioning
confidence: 99%
“…Flavor compound Raigond et al (2015) reported that the potato chips of different brands in the market showed the presence of flavor compounds concentration ranged from 5.9 to 9.8 lg/ g FW. The flavor compound (Umami/5 0 -nucleotide) was found to be 8.8 and 2.51 lg/g FW in control and calciumfortified potato chips which is approximately four times lesser than the commercially available chips.…”
Section: Correlation Between Blanching and Solid Loss And Oil Absorptmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its compositional characteristics, potato can be a good substitute for cereal crops and is gluten‐free. Potatoes have been widely used in many products such as instant dried noodle (Javaid et al, ), potato chips (Mariotti et al, ), French fries (Yang, Achaerandio, & Pujolà, ), and snacks (Raigond, Singh, Dhulia, Chopra, & Dutt, ). These studies have shown that the addition of potato makes a significant contribution to maintain the quality characteristics of products due to its starch content, structural protein differences, and type of protein (Bártová et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its compositional characteristics, potato can be a good substitute for cereal crops and is gluten-free. Potatoes have been widely used in many products such as instant dried noodle (Javaid et al, 2018), potato chips (Mariotti et al, 2015), French fries (Yang, Achaerandio, & Pujolà, 2016), and snacks (Raigond, Singh, Dhulia, Chopra, & Dutt, 2015).…”
mentioning
confidence: 99%